2017
DOI: 10.1186/s12913-017-2140-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hospital length of stay and direct costs of type 2 diabetes in Hubei Province, China

Abstract: BackgroundThe incidence of type 2 diabetes is increasing, creating a huge burden for China’s social healthcare system. This study aimed to evaluate hospital length of stay (LOS) based on admission characteristics and direct costs correlated with various types of complications for type 2 diabetic inpatients in Hubei Province, China.MethodsA total of 1528 inpatients diagnosed with type 2 diabetes discharged between April 1, 2013, and March 31, 2014, were included in this study. Information regarding patients’ ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
2
20
1
3
Order By: Relevance
“…The total annual direct cost per patient increased with the number of complications (Figure 1), primarily driven by inpatient and medication costs. The mean direct costs per patient associated with incident, acute macrovascular, microvascular, and metabolic complications ranged from €11,548 (acute coronary syndrome, France) [172] to €26,090 (incident cardiovascular disease [CVD], UK [173]) in EST markets and from €1,504 (ischemic heart disease, China [174]) to €8,786 (acute myocardial infarction, China [175]) in EMG markets. The mean direct costs per episode per patient associated with the management of chronic comorbidities ranged from €1,323 (retinopathy, Italy [176]) to €9,497 (established CVD, UK [173]) in EST markets and from €769 (microvascular disease, China [177]) to €4,865 (chronic kidney disease (CKD), China [178]) in EMG markets (Figure 2).…”
Section: Epidemiology: Complicationsmentioning
confidence: 99%
“…The total annual direct cost per patient increased with the number of complications (Figure 1), primarily driven by inpatient and medication costs. The mean direct costs per patient associated with incident, acute macrovascular, microvascular, and metabolic complications ranged from €11,548 (acute coronary syndrome, France) [172] to €26,090 (incident cardiovascular disease [CVD], UK [173]) in EST markets and from €1,504 (ischemic heart disease, China [174]) to €8,786 (acute myocardial infarction, China [175]) in EMG markets. The mean direct costs per episode per patient associated with the management of chronic comorbidities ranged from €1,323 (retinopathy, Italy [176]) to €9,497 (established CVD, UK [173]) in EST markets and from €769 (microvascular disease, China [177]) to €4,865 (chronic kidney disease (CKD), China [178]) in EMG markets (Figure 2).…”
Section: Epidemiology: Complicationsmentioning
confidence: 99%
“…Studies have demonstrated that people with diabetes are at higher risk of hospitalization [ 8 , 9 , 10 , 11 ] and readmission than people without diabetes [ 12 , 13 ]. The diabetes economic burden is significant and is expected to increase over time.…”
Section: Introductionmentioning
confidence: 99%
“…Another noteworthy point is that Chinese doctors tend to be more conservative and cautious in ensuring that patients achieve a stable state before discharging them from hospital, their motivation being to avoid potential challenges, legal action, or even threats from patients or their families, as have occurred in association with tense doctor–patient relationships in China, especially in recent years [ 21 , 22 ]. All the above reasons likely contribute to the much longer LOS for both patients with prostate cancer and those with other diseases [ 15 , 17 , 23 ] in China than in Western studies.…”
Section: Discussionmentioning
confidence: 99%